ON THE APPLICATION OF EARLY RELEASE ON PAROLE FOR PERSONS SENTENCED TO LIFE IMPRISONMENT - Коломієць, Наталія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Goal: outline the purpose of punishment. To characterize the basic rights of personessentenced to life imprisonment, as defined by the Convention for the Protection of Human Rights and Fundamental Freedoms. Analyze the decisions of the European Court of Human Rights on the protection of the rights of convicts in Ukraine and other countries. To find out the necessity and expediency of the application of early release on parole for persons sentenced to life imprisonment. Methods: general and specific scientific (special) methods were used to achieve the research goal. Results: the introduction of anearly release on parole from life imprisonment would greatly enhance the protection of the rights and freedoms of individuals, in particular those sentenced to life imprisonment, and would continue the policy of Ukraine on European standardization of laws. Discussion: the author finds out whether it is expedient to apply early release on parole for persons sentenced to life imprisonment.